Real-world python : a hacker's guide to solving problems with code - Vaughan, Lee (No Starch Press, Inc., 2021)
"A book of varied coding projects for readers who know a little Python already and want to expand their skills. Save shipwrecked sailors, discover exoplanets, and more, while gaining experience using free modules like OpenCV, NumPy, Pandas, NLTK, Bokeh, Beautiful Soup, and matplotlib"--